Reconstruction of Medium to Large Scalp Defects by Progressive Tightening of Pulley Sutures for Staged Primary Closure. Issue 6 (June 2020) - Croley, Julie A.; Malone, C. Helen; Hirshburg, Jason M.; Wagner, Richard F.
Abstract : Supplemental Digital Content is Available in the Text.